Effects of Inflation on Capital Structure - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1988)
A study was undertaken to examine the aggregate capital structure based on factors that affect the demand for and supply of corporate debt. It is suggested that the equilibrium level of aggregate corporate debt is determined by the following effects: 1. the Miller Effect (1977), which shows that there is a positive relationship between the aggregate corporate debt level and the yield spread between corporate and municipal bonds, 2. the Schall Effect (1984), which shows the relationship between aggregate corporate debt level and the yield spread between corporate bonds and equities to be positive, and 3. the DeAngelo-Masulis Effect (1980), which shows that a firm's debt ratio is linked negatively to the size of its depreciation deduction. It was found that, under the larger inflation, the amount of depreciation and the larger the yield differences between corporate and municipal bonds and equities, the larger the amount of corporate debt. Empirical data support these hypotheses.